2006
DOI: 10.1111/j.1600-0625.2006.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards the development of a pragmatic technique for isolating and differentiating nestin‐positive cells from human scalp skin into neuronal and glial cell populations: generating neurons from human skin?

Abstract: Nestin+ hair follicle-associated cells of murine skin can be isolated and differentiated in vitro into neuronal and glial cells. Therefore, we have asked whether human skin also contains nestin+ cells, and whether these can be differentiated in vitro into neuronal and/or glial cell populations. In this methodological pilot study, we show that both are indeed the case - employing purposely only very simple techniques for isolating, propagating, and differentiating nestin+ cells from normal human scalp skin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 34 publications
3
65
2
Order By: Relevance
“…[42][43][44] From the literature quoted so far and from our own results it is apparent that nestin expression apart from activated melanocytes is confined to mesodermally derived cells (CTS and endothelial cells). Our results are supported by a study from Kruse et al 45 Staining pattern for nestin is identical with 3 different nestin antibodies. All 3 nestin antibodies display identical staining pattern in regard to all anatomic structures of all different tissue samples examined.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…[42][43][44] From the literature quoted so far and from our own results it is apparent that nestin expression apart from activated melanocytes is confined to mesodermally derived cells (CTS and endothelial cells). Our results are supported by a study from Kruse et al 45 Staining pattern for nestin is identical with 3 different nestin antibodies. All 3 nestin antibodies display identical staining pattern in regard to all anatomic structures of all different tissue samples examined.…”
Section: Discussionsupporting
confidence: 93%
“…Original magnifications: A to C, Hair germ stage, 14 weeks (3400); D to F, bulbous hair peg stage, 19 weeks (3100); G to I, lower stem and hair bulb of postnatal hair follicle (3200); and J to L, BCC (3200). m J AM ACAD DERMATOL VOLUME 63, NUMBER 1 et al 46 We suspect technical differences in the procedure used by these authors for this discrepancy in the immunohistochemical findings between our results and those of Kruse et al 45 46 We used the same mouse monoclonal antibody from Santa Cruz Biotechnology as Wang et al 46 and confirmed our results different from theirs with two other antibodies.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The intermediate filament protein nestin is expressed by peripheral nerves adjacent to the hair follicle bulge and by neural crest stem cells, melanocyte precursors and dermal papilla cells (Amoh et al, 2005;Dunn et al, 2000;Kruse et al, 2006;Li et al, 2003;Tiede et al, 2007). In K14NICDER mice treated with 4OHT for 14 days, there was marked accumulation of nestin-positive cells at the epidermal-dermal boundary (Fig.…”
Section: Epidermal Notch Activity Results In Accumulation Of Dermal Cmentioning
confidence: 99%